Public policy, markets and household coping strategies in Bangladesh: avoiding a food security crisis following the 1998 floods - del Ninno, Carlo; Dorosh, Paul A.; Smith, Lisa C. (Elsevier, 2003)
At their peak, the 1998 floods covered two-thirds of Bangladesh, causing severe damage to the major rice crop and threatening the food security of tens of millions of households. In this paper, we first highlight the contribution of government policy interventions, including trade liberalization in the early 1990s, to stabilization of rice markets during and after the flood. Then, using a panel data set covering 750 households in three rounds over a 13-month period, we analyze impacts of the flood on household assets, consumption and nutritional outcomes. Finally, we present empirical estimates of the contribution of rice market stabilization and government transfers to household food consumption.